Transformasi Struktur Sekolah Menuju Pendidikan Islami Holistik: Studi Literatur tentang Integrasi Nilai PAI - Muhammad Mauludi Kurniawan Wawan; Muhyiddin; M. Rizal Hardiansyah; Jakaria Umro (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2026)
The abstract provides a comprehensive overview or a concise summary This study aims to analyze the transformation of school structures toward holistic Islamic education through the integration of Islamic Religious Education (PAI) values. The method used is library research with a descriptive qualitative approach, by analyzing relevant scientific literature from the last five years. The findings indicate that the transformation of school structures not only involves curriculum aspects but also includes school culture, institutional management, and the role of teachers as role models of Islamic values. The holistic integration of PAI values contributes to shaping students who are not only academically competent but also possess strong spiritual, moral, and social awareness. This study concludes that the success of transforming holistic Islamic education depends on the synergy between institutional structures, value implementation, and the commitment of all school stakeholders.